The Use Of Pictured Stories In Improving Students Vocabulary Achievement - Budi Kadaryanto; Emi Handayani (LINGUISTIKA, 2011)
The objective of this research was to find out whether there was any significant improvement of the studentsâ vocabulary achievement at the eighth grade of SMP Tunas Harapan, Kedaton, Bandar Lampung after they were taught by using pictured stories and to investigate the process of teaching vocabulary by using pictured stories. This research used one group pre test post test design. The sample of this research was VIII A at Tunas Harapan, Kedaton, Bandar Lampung, in academic year 2010/2011. Objective vocabulary test was used as the instrument of the research. The data were analyzed by using repeated measure t- test in which the significance was determined by p<0.05. The result suggested that the difference of the mean score from pretest and posttest was 16.4. Under SPSS test, the difference was significant, in which the p value was 0.000, which was less than 0.05. This indicates the significant improvement of students vocabulary achievement. In addition the teaching learning process using pictured stories indicates that can improve the students involvement and students activeness in the process of teaching learning vocabulary.